Results dissemination and stakeholders workshop report in Makueni, Nakuru and Embu, Kenya - Lutomia, Cosmas; Nyamolo, victor; Ketema, Dessalegn; Nchanji, Eileen; Waswa, Boaz; Ooro, Patrick; Muriithi, Catherine; Njiru, Emerita; Ingasia, Oscar; Jong, Arnold (2024)
The results dissemination workshop by the work package 2 HER+ (Gender Equality initiative) was meant to provide evidence and get validation from the key stakeholders, including farmers and partners, on the impact of integrating socio-technical innovation bundles. The implementation sites are nested with the Utama Ustawi (UU) initiative. The workshops were conducted between the 8th and 16th of April 2024 in Nakuru, Embu, and Makueni. The workshop’s objectives were to share tangible benefits of socio-technical bundles resulting in empowerment, resilience, mechanization and food and nutrition security for the farmers. In addition reflect on the challenges and learnings from implementing the socio-technical innovation bundles (STIBs) in Nakuru, Embu and Makueni. The workshops also aimed to foster dialogue to identify challenges, opportunities, and practical solutions for scaling STIB adoption. Additionally, it sought feedback from stakeholders on the implementation of STIBs to continuously enhance the co-design interventions and innovations while strengthening existing partnerships for the successful implementation and adoption of STIBs.